Multiplying menace : the revenge of Rumpelstiltskin : a math adventure - Calvert, Pam, 1966-; Geehan, Wayne (Watertown, MA : Charlesbridge, 2006)
Ten years after being tricked, Rumpelstiltskin returns to the royal family to wreak vengeance using multiplication. Includes nonfiction math notes about multiplying by whole numbers and by fractions.
Horn Book
School Library Journal
Wilson's Children
Horn Book, October 2006
School Library Journal, April 2006
Science Books & Films (A.A.A.S.), March 2007
Keywords: Characters in literature -- Juvenile fiction; Multiplication -- Juvenile fiction; Characters in literature -- Fiction; Multiplication -- Fiction; Characters and characteristics in literature -- Fiction; Multiplication -- Fiction